2022
DOI: 10.1177/03063070211059956
|View full text |Cite
|
Sign up to set email alerts
|

The impact of doctors’ career calling on organizational citizenship behavior mediated by work–life balance and job satisfaction

Abstract: The present study explored the relationship between doctors’ career calling and organizational citizenship behavior (OCB). A model proposing that the effect of career calling on OCB mediated by work–life balance (WLB) and job satisfaction was assessed. Data were collected from 670 doctors working in hospitals across Northern India out of which 325 questionnaires were considered for analysis purpose. The results demonstrated that career calling has a significant effect on OCB and WLB and job satisfaction mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…These insights suggest the possibility of resource transfer from work to personal life and vice versa that enhances overall quality of life. More specifically, in the Indian context, research by Nayak (2016), Shabir and Gani (2020) and Vashisht and Vashisht (2022), has indicated the presence of WFE among healthcare professionals, as demonstrated by low turnover intention, high organizational commitment and better organizational citizenship behavior. These findings provide a foundation for the exploration of WFE among healthcare professionals in the Indian context.…”
Section: Work-family Interface Among Indian Doctorsmentioning
confidence: 99%
See 2 more Smart Citations
“…These insights suggest the possibility of resource transfer from work to personal life and vice versa that enhances overall quality of life. More specifically, in the Indian context, research by Nayak (2016), Shabir and Gani (2020) and Vashisht and Vashisht (2022), has indicated the presence of WFE among healthcare professionals, as demonstrated by low turnover intention, high organizational commitment and better organizational citizenship behavior. These findings provide a foundation for the exploration of WFE among healthcare professionals in the Indian context.…”
Section: Work-family Interface Among Indian Doctorsmentioning
confidence: 99%
“…, 2020). This outlook is echoed in the Indian context by studies reporting low turnover intention, high organizational commitment and strong organizational citizenship behavior among healthcare professionals (Nayak, 2016; Shabir and Gani, 2020; Vashisht and Vashisht, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From another approach, it is evident that professional careers have a significant impact on organizational citizenship behavior (OCB) and WLB. Thus, WLB and job satisfaction may indicate a critical link between career and organizational citizenship behavior [96]. Another study indicates that workers claim to have difficulties reconciling work and family, and one-third consider leaving their job for these reasons [97].…”
Section: Wlb and Job Satisfaction In Remote Workmentioning
confidence: 99%